Climate change, the environment, and rhinologic disease. Issue 5 (16th January 2023) - Kim, Jean; Waugh, Darryn W; Zaitchik, Benjamin F; Luong, Amber; Bergmark, Regan; Lam, Kent; Roland, Lauren; Levy, Joshua; Lee, Jivianne T; Cho, Do‐Yeon; Ramanathan, Murugappan; Baroody, Fuad; et al.
Abstract: Background: The escalating negative impact of climate change on our environment has the potential to result in significant morbidity of rhinologic diseases. Methods: Evidence based review of examples of rhinologic diseases including allergic and nonallergic rhinitis, chronic rhinosinusitis, and allergic fungal rhinosinusitis was performed. Results: The lower socioeconomic population, including historically oppressed groups, will be disproportionately affected. Conclusions: We need a systematic approach to improve healthcare database infrastructure and funding to promote diverse scientific collaboration to address these healthcare needs.